Postexercise cold water immersion modulates skeletal muscle PGC-1α mRNA expression in immersed and nonimmersed limbs: evidence of systemic regulation - Allan, Robert; Sharples, Adam P.; Close, Graeme L.; Drust, Barry; Shepherd, Sam O.; Dutton, John; Morton, James P.; Gregson, Warren (Journal of applied physiology (1985), 2017)
Mechanisms mediating postexercise cold-induced increases in PGC-1α gene expression in human skeletal muscle are yet to be fully elucidated but may involve local cooling effects on AMPK and p38 MAPK-related signaling and/or increased systemic β-adrenergic stimulation. Therefore, we aimed to examine whether postexercise cold water immersion enhancement of PGC-1α mRNA is mediated through local or systemic mechanisms. Ten subjects completed acute cycling (8 × 5 min at ~80% peak power output) followed by seated-rest (CON) or single-leg cold water immersion (CWI; 10 min, 8°C). Muscle biopsies were obtained preexercise, postexercise, and 3 h postexercise from a single limb in the CON condition but from both limbs in CWI [thereby providing tissue from a CWI and nonimmersed limb (NOT)]. Muscle temperature decreased up to 2 h postexercise following CWI (−5°C) in the immersed limb, with lesser changes observed in CON and NOT (−3°C, P < 0.05). No differences between limbs were observed in p38 MAPK phosphorylation at any time point ( P < 0.05), whereas a significant interaction effect was present for AMPK phosphorylation ( P = 0.031). Exercise (CON) increased gene expression of PGC-1α 3 h postexercise (~5-fold, P < 0.001). CWI augmented PGC-1α expression above CON in both the immersed (CWI; ~9-fold, P = 0.003) and NOT limbs (~12-fold, P = 0.001). Plasma normetanephrine concentration was higher in CWI vs. CON immediately postimmersion (860 vs. 665 pmol/l, P = 0.034). We report for the first time that local cooling of the immersed limb evokes transcriptional control of PGC-1α in the nonimmersed limb, suggesting increased systemic β-adrenergic activation of AMPK may mediate, in part, postexercise cold induction of PGC-1α mRNA. NEW & NOTEWORTHY We report for the first time that postexercise cold water immersion of one limb also enhances PGC-1α expression in a contralateral, nonimmersed limb. We suggest that increased systemic β-adrenergic stimulation, and not localized cooling per se, exerts regulatory effects on local signaling cascades, thereby modulating PGC-1α expression. Therefore, these data have important implications for research designs that adopt contralateral, nonimmersed limbs as a control condition while also increasing our understanding of the potential mechanisms underpinning cold-mediated PGC-1α responses.